Development and validation of a short version of the Female Sexual Function Index in the Spanish population - Laura Mateu Arrom; Montserrat Girabent-Farrés; Mónica González; Joan Palou; Carlos Errando-Smet; Inés Ramírez-García (BMC, 2021)
Abstract Background The Female Sexual Function Index (FSFI) is a commonly used scale for the assessment of female sexual function. Our aim was to develop and validate a Spanish short version of the FSFI. Methods A parallel exploratory, sequential mixed-methods approach was used, involving 2 sites. The process consisted of 2 steps: (1) cognitive and content validation of the previously translated FSFI in the Spanish population, both through a focus group; and item selection based on the difficulty and discrimination parameters using item response theory (IRT), thereby obtaining a short version of the scale (sFSFI-sv); (2) assessment of test-retest reliability (intraclass correlation coefficient, ICC) of the sFSFI-sv. The presence or absence of a sexual disorder variable based on clinical interview was used on the Receiver Operating Characteristic (ROC) to establish the cut off point whose Area Under the Curve (AUC) based on sensibility and specificity was maximum. Results Specific modifications of the FSFI were made according to the focus group results. 114 women were included for IRT analysis. The initial IRT model pointed to the exclusion of items 1, 2, 5, 11, 18, and 19 (S-χ2 p < 0.001). Items 3, 9, 11, and 14 showed the best discrimination and difficulty parameters. On the basis of the IRT and focus group results, items 1, 3, 9, 12, 16, and 17 were included in the final sFSFI-sv. sFSFI-sv showed good reliability (ICC 0.91) in a group of 93 women. A total score ≤ 18 could indicate a higher risk of sexual disorder (sensitivity: 81.0%, specificity: 73.3%). Conclusion A focus group and the IRT analysis allowed the development of a 6-item Spanish version of the FSFI, which showed good reliability in a group of Spanish women.